ROLE OF MORPHOLOGICAL AND GENETIC STRUCTURAL CHARACTERISTICS OF ESTROGEN RECEPTOR ALPHA IN THE DEVELOPMENT OF RESISTANCE TO ENDOCRINOTHERAPY WITH TAMOXIFEN IN PATIENTS WITH LUMINAL BREAST CANCER - Е. М. Slonimskaya; S. V. Vtorushin; N. N. Babyshkina; S. V. Patalyak (Сибирский онкологический журнал, 2016)
Hormone therapy with tamoxifen is the commonly used treatment for luminal breast cancer. However, it appears to be ineffective in 20–40 % of cases and the possible reasons of this failure are related to the features of distribution and structure of estrogen receptor alpha (ERα) in tumor tissue. Realization of the therapeutic effect of tamoxifen is carried out by blocking the activation center of AF-2 receptor. The change in the functional state of this receptor resulted from single-nucleotide polymorphisms coding 2228480 (G/A) in exon 8 of ERα gene is considered as a possible cause of treatment failure with tamoxifen.The purpose of the study was to analyze the relationship between the ERα expression and polymorphic variants in exon 8 of the ERα gene and the efficacy of tamoxifen in patientswith luminal breast cancer.Material and methods: The study included 97 patients with stage T1–2N0–1M0 luminal breast cancer, who received adjuvant chemotherapy with tamoxifen. The follow-up ranged from 24 to 130 months. Long-term treatment outcomes were assessed upon the progression of the disease with the evidence of distant metastases. In tumor tissue samples, the ERα expression was studied using the immunohistochemical method. The values of the ERα expression intensity as well as the character of ERα distribution were assessed. Polymorphic variants of exon 8 of the ERα gene were studied using real-time PCR.Results. The heterogeneous distribution of ERα gene was observed in 86.5 % cases with diseases progression and in 58.3 % of cases with favorable disease outcome (р=0.0072; χ2 =7.22). Mutation of rs2228480 (G/A) in exon 8 of the ERα gene was observed in 19.4 % of cases. Mutations were not noted in tumor cells with homogenous distribution of the ERα gene and mutations were found in 25.7 % (р=0.014; χ2 =6.09) in heterogeneous distribution. Mutation in exon 8 of the ERα gene was shown to occur more often in patients with disease progression (р=0.01; χ2 =6.52).Conclusion: The character of the ERα gene distribution and the presence of mutation in exon 8 of the ERα gene in tumor tissue can be considered as additional predictive factors of response to therapy with tamoxifen in patients with luminal breast cancer.